Calcium and vitamin D supplementation do not influence menopause-related symptoms: Results of the Women's Health Initiative Trial. Issue 3 (July 2015) - LeBlanc, Erin S.; Hedlin, Haley; Qin, FeiFei; Desai, Manisha; Wactawski-Wende, Jean; Perrin, Nancy; Manson, JoAnn E.; Johnson, Karen C.; Masaki, Kamal; Tylavsky, Frances A.; Stefanick, Marcia L.
Highlights Women on calcium/vitamin D did not have fewer menopausal symptoms than placebo women. Calcium/vitamin D was not associated with sleep quality, mental health, or fatigue. Calcium/vitamin D did not improve wellbeing in women with an average age of 64 years.